PARTICULATE MATTER POLLUTION IN NIGERIA: A REVIEW - Taiwo, Adewale M.; Arowolo, T. A.; Abdullahi, Karimatu (2015)
Particulate Matter (PM) is a major air pollutant in the Nigeria atmospheric environment. This study has reviewed PM pollution in all the geopolitical zones in Nigeria. Published works relating to PM pollution in Nigerian cities were accessed and analysed. Data collected showed a high total concentration of total suspended particle (TSP) varying between 1,033 to 40,000 µg/m 3 and also a PM10 concentration range of 118.3 -132.0 µg/m3. Most of the reported PM mass concentrations in Nigeria were higher than the annual World Health Organization (WHO) standards of 90 µg/m3 for TSP and the USEPA standard of 40 µg/m 3 for PM10. In terms of apportionment, the mostly used receptor models were Principal Component Analysis (PCA) and Chemical Mass Balance (CMB). The major emission sources identified by these models were traffic, industry, soil, sea spray and biomass burning. The source apportionment study conducted in Lagos showed marine and crustal matter as the highest PM sources contributing 76% and 58% to coarse and fine PM, respectively. In the northern part of Nigeria, the major emission sources of is wind-blown dust from the Sahara desert. PM pollution is therefore a serious concern in Nigeria that required urgent mitigating measures. This may result into major health problems such as cardio-vascular and respiratory diseases as well as ill-effects on the environment.
openalex: W2344104467 mag: 2344104467
Keywords: openalex:import

Assessing the pollution effect of cement dust emission on the soil quality around Ewekoro cement factory, southwestern Nigeria - Taiwo, Adewale M.; Taiwo, Adewale M.; Adeofun, C. O.; Adetunji, M. T.; Azeez, J. O.; Arowolo, T. A. (Environmental Forensics, 2022)
This study assessed the pollution effects of cement dust emission on the soil quality around Ewekoro, southwestern Nigeria. Composite soil samples were collected at six locations from the cement factory (0 km) to a distance of 3 km outside the factory; for two consecutive years. Soil samples were also taken from a distance of 22 km after the cement factory to serve as a control. A total of 42 soil samples were collected and subjected to laboratory assays using standard procedures. Samples were analyzed for pH, organic carbon, particle size, available phosphorus (AvP), alkalinity, exchangeable cations, and heavy metals. Data collected were subjected to simple descriptive and inferential statistics using SPSS for Windows. Pollution effect was also evaluated for pollution index (PI), ecological risk index (ERI), Nemerov integrated pollution index (NIPI), and enrichment factor (EF). Results showed significantly higher levels of exchangeable cations, alkalinity, AvP, pH, Cr, Cu, Pb, and Fe in the vicinity of the cement factory than in the control site. The distribution of metals in soils around the cement factory followed the trend of Fe > Mn > Zn > Pb > Cr > Cu. The PI of metals in soil established high pollution levels for Pb and Zn. The NIPI values for Cu, Cr, and Fe showed low levels of pollution at the vicinity of the cement industry, while no pollution level was observed at the control site. NIPI revealed that Pb varied from low to moderate pollution levels across the sampling locations. The EF values of Zn and Pb were higher than 2.0, thereby suggesting emissions from anthropogenic activities, especially from the cement industry.
openalex: W4296700429
Keywords: openalex:import

Heavy Metals Content in Playground Topsoil of Some Public Primary Schools in Metropolitan Lagos, Nigeria - Popoola, Oluseun E.; Bamgbose, O.; Okonkwo, O. J. Prof.; Arowolo, T. A.; Odukoya; Popoola, Abiodun (Research Journal of Environmental and Earth Sciences, 2012)
Assessing the concentration of potentially harmful heavy metals in playground topsoil from public primary schools in metropolitan Lagos, is imperative in order to evaluate the potential risks to the children in the schools. The study was conducted in order to determine if the concentrations of heavy metals in the soil is high enough to constitute a risk to children. Samples were collected from 20 schools in the Lagos metropolis and were subjected to microwave aqua regia digestion. Subsequently, the concentrations of the metals in the samples were measured using Graphite Furnace Atomic Absorption Spectrometry (GFAAS). The investigation revealed that Pb has the highest concentrations of all the metals. Mean metal concentration in playground soils were Pb_(HD) 23.08±11.11, Pb_(LD) 23.54±14.55; Cr_(HD) 5.99±5.79, Cr_(LD) 3.80±3.83; Cd_(HD) 0.33±0.33, Cd_(LD) 0.39±0.31; Mn_(HD) 1.60±0.14, Mn_(LD) 1.61±0.05 :g/g. Univariate analysis of variance showed that the metal concentrations in the high or low population density areas were not significantly different (p＞0.05). The results generally indicated that pollution by metals in the dusts and soils is minimal for Pb and Cr and negligible for Mn and Cd while geographical location of the schools in high and low population density areas of Lagos state, Nigeria was not a determinant in the evaluation of children's exposure to heavy metals.
openalex: W2181735251 mag: 2181735251
Keywords: openalex:import

Elemental Profiling, Pollution and Health Risks Assessments of Classroom Dust from Selected Nursery and Kindergarten Schools Ogun State, Nigeria - Oyebanji, F. F.; Olatunde, K.A.; Kasumu, Habiblahi Olabode; Akinola, Tosin Samson; Afinuomo, Adebayo; Tiamiyu, Olaide; Ogunnowo, Kolade David; Arowolo, T. A. (Environmental Research, Engineering and Management, 2023)
Knowing the concentration of elements in children’s classroom dust and the associated ecological and health risks is essential in preventing and controlling possible elemental poisoning. Dust samples were collected from 37 nursery and kindergarten classrooms across three local government areas in Abeokuta, Nigeria, and assessed for elemental concentrations using X-ray fluorescence (XRF) spectrophotometry. The hazard and the cancer risk indexes were estimated using the geo-accumulation index (Igeo) and health risks posed to children. The highest mean concentrations (mg/kg) of Ca, Fe, K, and Ti ranged between 4034.22–15995.09, 1758.95–2409.62, 5146.66–8996.75, and 730.96–1140.38, respectively. About 33.33% of the monitored metals displayed Igeo values within the moderately polluted and extremely polluted categories in Abeokuta South and North. All the monitored locations were strongly polluted with Ca, Fe, K and Ti, including arsenic at Abeokuta South. Metals with high pollution (Cf > 6) were Ca, Fe, Co, As, K, Ti and Ge in Abeokuta South. Ca, Fe, Co, As, K, Sc, Ti and Ge in Abeokuta North; and Ca, Fe, As, K, Sc, Ti and Ge at Odeda. Arsenic levels were 128.42 (considerable), 2934.27 (very high) and 179.33 (high) for the ecological risk factors. Dust samples for Abeokuta South and North posed the least and greatest ecological risks, respectively, and the risk potentials of arsenic across all the locations were in the ecologically risky ranges. However, hazard indexes < 1 were recorded across the monitored sites, indicating no immediate non-carcinogenic health risks, while cancer risks for Co, Ni, As, and Cr were < 1.0E−04, respectively, depicting no significant carcinogenic risk. This study concluded that the levels of elements monitored do not pose any health risk to the children but are of concern to the ecosystem. Therefore, policies on locating schools in areas with minimum anthropogenic pollution should be formulated and continuous cleaning of classroom surfaces should be encouraged.
openalex: W4387604072
Keywords: openalex:import